Silver nanoparticles with plasma-polymerized hexamethyldisiloxane coating on 3D printed substrates are non-cytotoxic and effective against respiratory pathogens - Machková, Anna; Vaňková, Eva; Obrová, Klára; Fürhacker, Paola; Košutová, Tereza; Lion, Thomas; Hanuš, Jan; Scholtz, Vladimír (Frontiers in Microbiology, 2023)
Due to the emerging resistance of microorganisms and viruses to conventional treatments, the importance of self-disinfecting materials is highly increasing. Such materials could be silver or its nanoparticles (AgNPs), both of which have been studied for their antimicrobial effect. In this study, we compared the biological effects of AgNP coatings with and without a plasma-polymerized hexamethyldisiloxane (ppHMDSO) protective film to smooth silver or copper coatings under three ambient conditions that mimic their potential medical use (dry or wet environments and an environment simulating the human body). The coatings were deposited on 3D printed polylactic acid substrates by DC magnetron sputtering, and their surface morphology was visualized using scanning electron microscopy. Cytotoxicity of the samples was evaluated using human lung epithelial cells A549. Furthermore, antibacterial activity was determined against the Gram-negative pathogenic bacterium Pseudomonas aeruginosa PAO1 and antiviral activity was assessed using human rhinovirus species A/type 2. The obtained results showed that overcoating of AgNPs with ppHMDSO creates the material with antibacterial and antiviral activity and at the same time without a cytotoxic effect for the surrounding tissue cells. These findings suggest that the production of 3D printed substrates coated with a layer of AgNPs-ppHMDSO could have potential applications in the medical field as functional materials.